2018
DOI: 10.1186/s12906-018-2315-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of acute, 14-day, and 13-week repeated oral dose toxicity of Tiglium seed extract in rats

Abstract: BackgroundSeed of mature Croton tiglium Linne, also known as Tiglium seed (TS), has been widely used as a natural product due to its several health beneficial properties including anti-tumor and antifungal activities. Despite its ethnomedicinal beneficial properties, toxicological information regarding TS extract, especially its long-term toxicity, is currently limited. Therefore, the objective of the present study was to evaluate acute and subchronic toxicity of TS extract in rats after oral administration fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Protein profile and metabolic biomarkers were also measured. Serum levels of three enzymes (ALT, AST, and ALP) are commonly used as clinical biochemistry markers associated with liver damage [ 33 35 ]. Among these enzymes, serum levels of ALT and AST of the groups 500, 1000, and 2000 mg/kg/bw were statistically lower when compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Protein profile and metabolic biomarkers were also measured. Serum levels of three enzymes (ALT, AST, and ALP) are commonly used as clinical biochemistry markers associated with liver damage [ 33 35 ]. Among these enzymes, serum levels of ALT and AST of the groups 500, 1000, and 2000 mg/kg/bw were statistically lower when compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate the toxicity of any new compound, it is necessary to understand the status of these two important organs, which can be validated through biochemical evaluation ( Sureshkumar et al, 2018 ). Serum levels of three enzymes (ALT, AST, and ALP) are commonly used in studies as clinical biochemical markers related to liver injury ( Yun et al, 2018 ). Our results showed no significant differences in their serum levels between all groups.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical analysis by LC-MS/MS revealed the presence of nine alkaloids in the hydroethanolic extracts: trisphaeridine, galanthamine, crinine, demethylmaritidine, anhydrolycorine, nor-galanthamine, N-formylnorgalanthamine, peramine, and ergovaline. Several studies have identified the presence of alkaloids, but no study has identified these alkaloid types [ 45 ]. Sterols, saponins, and phenolic compounds have all been reported as secondary metabolites of this plant.…”
Section: Discussionmentioning
confidence: 99%
“…Sterols, saponins, and phenolic compounds have all been reported as secondary metabolites of this plant. A recent study demonstrated that D. ambrosioides contains alkaloids [ 45 ]. This finding correlates with our results.…”
Section: Discussionmentioning
confidence: 99%